Visit ka Binong: Strengthening Branding and Customer Experience of Binong Tourism Urban Village Based on Empowerment of Tourism Awareness Groups (Pokdarwis) - Daniel Hermawan; Yoke Pribadi Kornarius; Albert Mangapul Parulian Lumban Tobing; Syayu Zhukhruffa (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Binong Tourism Urban Village is a tourism urban village declared by the Bandung City Culture and Tourism Office based on Bandung Mayor Decree Number 556/Kep.835-DISBUDPAR/2021 dated 16 September 2021. This initiative was carried out by the Bandung City Culture and Tourism Office to develop the potential of Binong Urban Village, in addition to the knitting industry center that has been known for generations. The mentoring process in the initiation, identification, and implementation of the Binong Tourism Urban Village was carried out collaboratively between the Bandung City Culture and Tourism Office, STIEPAR Yapari Bandung, and Parahyangan Catholic University. Through the mentoring process carried out, the Binong Urban Village managed to form a Tourism Awareness Group (Pokdarwis) and get a change in mindset related to branding and the customer experience of the Binong Tourism Urban Village. The sustainability of the mentoring program can be carried out through the MBKM program with the thematic KKN scheme, as well as deepening the material needed by the community, especially related to tourism marketing.